EVALUASI SISTEM DRAINASE RUAS JALAN LOKKI - IHA KULUR DESA LUHU KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Notanubun, Aldi; Betaubun, Renny James; Johanes, Standi (Journal Agregate, 2023)
The Lokki – Iha Kulur Road Section is the main transportation route that connects villages in Huamual District, West Seram District. This area often experiences inundation and runoff caused by drainage that cannot accommodate flood discharge and improper drainage elevation systems. To overcome this problem, it is necessary to review the drainage system. The research method used is the method of data collection and analysis. The data used are primary data and secondary data and then analyzed using rational methods based on hydrological analysis and hydraulics analysis and evaluated based on the magnitude of the discharge of the existing canal with the magnitude of the planned discharge. Based on the calculation results for a 5-year return period, a planned rainfall of 632.812 mm is obtained, with a population growth percentage of 1.2% per year so the population of Luhu Village in 2026 is 34,251 people. From the results of the analysis, it was found that the amount of planned discharge entering the Lokki – Iha Kulur Road drainage was 0.15038 m3/s for drainage 1 and 0.14377 m3/s for drainage 2. Meanwhile, the discharge for the Lokki – Iha Kulur Road drainage for drainage 1 is 0.14229 m3/sec and for the drainage 2 is  0.14377 m3/sec. So it was found that the drainage was not able to accommodate the planned flood discharge so it was necessary to re-plan the drainage dimensions so that the problems of inundation and runoff could be overcome.